Analysis of the Influence of Recruitment and Competence on the Performance of Group 3 Kopassus Personnel - Satrio Aribowo, Galih (Dinasti Publisher, 2025)
Group 3 Kopassus is one of the units in the Kopassus ranks that has the ability to multiply forces to complete selected strategic targets. In the face of modern challenges such as global terrorism, asymmetric warfare, and cyber threats, competency-based recruitment is key to ensuring personnel quality. This study aims to analyze the influence of recruitment and competency on the performance of Kopassus Group 3 personnel and evaluate the strategic recruitment process in supporting organizational sustainability. A qualitative approach with a case study design was used in this research, with direct observation methods to explore the dynamics of recruitment and competency development. The results show that rigorous competency-based recruitment contributes significantly to operational performance, although it takes a long time and can hinder the procurement of personnel in urgent situations. Key competencies that influence operational effectiveness include technical capabilities such as terrain navigation and infiltration, as well as nontechnical capabilities such as leadership and mental resilience. The conclusion of this study is the importance of balancing time efficiency with recruitment quality through process optimization without compromising standards. Suggestions are given to improve continuous training and recruitment support technology to strengthen adaptability and operational readiness.